AKTIVITAS ANTIDISLIPIDEMIA EKSTRAK ETANOL HERBA PEGAGAN (Centella asiatica L. Urb) PADA TIKUS WISTAR JANTAN OBESITAS YANG DIINDUKSI PAKAN TINGGI LEMAK DAN KARBOHIDRAT - Hendra Mahakam Putra; Aulia Nurfazri; Sonia Safitri (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
Dyslipidemia is an abnormality that occurs in the lipid profile. Obesity can affect lipid profile levels such as increased levels of triglycerides (TG), total cholesterol (KT), Low-Density Lipoprotein (LDL), and decreased High-Density Lipoprotein (HDL), known as dyslipidemia. This study aimed to determine the antidyslipidemic activity of the ethanol extract of Centella asiatica herb in rats induced by a high fat and carbohydrate diet. This research is an experimental prevention method using 6 groups of test animals that were induced for 60 days (except the normal group) accompanied by the administration of the test substance 2 hours before the induction was carried out. Group 1 as a normal control was only given Na-CMC, group 2 as an induced control was only given Na-CMC, group 3 was given fenofibrate suspension 18 mg/Kg BW, and groups 4-6 were given ethanol extract of Centella asiatica herb at a dose of 50 mg/Kg, 100 mg/Kg, and 200 mg/Kg BW. Parameters for examination of lipid profile levels including levels of TG, KT, HDL, and LDL were carried out on day 0 and day 60. The results showed that the administration of the ethanolic extract of Centella asiatica herb at a dose of 200 mg/Kg was effective in providing activity in maintaining normal levels of triglycerides, total cholesterol, and LDL. It can be concluded that the ethanol extract of Centella asiatica has antidyslipidemic activity in a rat model induced by a high fat and carbohydrate diet.